PHYSIOTHERAPY PARTICIPATION IN THE REVIEW AND DISSEMINATION OF CLINICAL PRACTICE GUIDELINE FOR THE MANAGEMENT OF PATIENTS WITH PARKINSON’S DISEASE (Cuestiones de Fisioterapia, 2016)
Introduction: one of the greatest challenges currently facing the Servicio Nacional de Salud is the increasing incidence of chronic diseases. Parkinson’s disease (PD) is a chronic neurodegenerative disorder with cumulative effects on patients and families, and the health and social systems. To facilitate the approach to the chronicity, it is of interest to develop a Clinical Practice Guide (CPG), as is the case with Parkinson’s disease (CPG-PD). The overall objective of this article is to improve the dissemination of CPG-PD. The specific objective is to present the role of physiotherapy professionals in the review process of the CPG-PD. Material and method: a literature search was performed in databases and specialized sources: Medline, Embase, the Cochrane Library, Centre for Reviews and Dissemination, Índice Bibliográ-fico Españolen Ciencias de la Salud and Literatura Latinoamericana y del Caribeen Ciencias de la Salud. Results: we developed 16 clinical questions, grouped into two main sections: pharmacological and non-pharmacological treatment. It has the support and participation of 15 associations, scientific societies or associations. Thirty-three health professionals: doctors, pharmacists, nurses, physical therapists, speech therapists, psychologists, occupational therapists and dieticians participated. Conclusion: the development of a CPG based on systematic review of the evidence is a personal, professional and economic continuous effort of considerable magnitude. The need to improve the return on investment through the dissemination and implementation of the recommendations is a priority.